Pembuatan Indeks Puisi di Rumah Puisi Taufik Ismail Padang Panjang - Irfan, Mhd.; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
This paper aimsto describe how indexes poetry at Rumah Puisi Taufik Ismail Padang Panjang. Data collected by direct observation in Rumah Puisi Taufik Ismail Padang Panjang. Based on the results of the discussion index creation poems in the Poetry House Taufik Ismail Padang Panjang this can be inferred through several stages as follows: (1) The initial observations of the document: to observe the documents to be indexed and made details on the document; (2) determine the main subject is in the manufacture of a required index determination to the main subject in this paper that became the main subject in the manufacture of this index is an index poems in the Rumah Puisi Taufik Ismail Padang Panjang; (3) create a description of the index; (4) in the indexing terms that must be included in accordance with the data obtained without changing it; (5) indexing language that is clear and precise; (6) make a title index; (7) and typing on the index as well as examination of the indices that have been typed to avoid errors.Keyword: indexes poetry, Rumah Puisi Taufik Ismail Padang Panjang.